Cerebral Microbleed Burden in Ischemic Stroke Patients on Aspirin: Prospective Cohort of Intracranial Hemorrhage - Xu, Chong-xi; Xu, Hui; Yi, Tong; Yi, Xing-yang; Ma, Jun-peng (Frontiers in Neurology, 2021)
Objective: This investigation aimed at studying the prevalence of cerebral microbleeds (CMBs), including risk parameters and the correlation of CMBs to ischemic stroke patient end results. Methods: 459 acute ischemic stroke (IS) cases were recruited between April 2014 and December 2016. CMBs were analyzed using susceptibility weighted imaging (SWI) brain magnetic resonance imaging (MRI) scan. All such clinical cases were assessed on a long-term basis (12-24 months). Clinical outcomes including recurrent ischemic stroke (RIS), intracranial hemorrhage (ICH), transient ischemic attack (TIA), mortality and cardiovascular events, were evaluated. The associations between vascular risk factors and CMBs in IS patients were analyzed using univariate and multivariate logistic regression analysis. Cox regression model was employed for evaluating CMB impact on clinical outcome. Results: Among 459 enrolled patients, 187 (40.7%) had CMBs and 272 (59.2%) had no CMB events. In comparison to patients with no CMBs, age was higher, hypertension was more frequent in patients with CMBs. Multivariate logistic regression analyses revealed age and hypertension to be independently correlated to CMBs. Among the patient cohort, 450 cases completed the follow-up. During the follow-up period, 22 (4.9%) of patients developed ICH, 12 (2.7%) developed TIA, 68 (15.1%) developed RIS, cardiovascular events occurred in 20 (4.44%), and 13 (2.89%) cases were mortalities. ICH prevalence was increased within the patient group with CMBs (P< 0.05). Notwithstanding, no statistically valid variations regarding other outcome incidences between both groups was identified (P > 0.05). The incidence of ICH was elevated in tandem with elevations in CMB events. Following adjusting for age, multivariate Cox proportional-hazards regression analysis revealed that CMBs≥10 were separate predictive manifestations for post-acute IS ICH. Conclusion: CMB manifestation is fairly high in acute IS. Age and hypertension are independently associated with CMB events. ICH incidence rate was exacerbated within patients manifesting CMB events, and CMBs≥10 were independent predictors of ICH across the 12-24 post-therapy assessment period.